ANALISIS FAKTOR PENYEBAB KETIDAKLENGKAPAN RESUME MEDIS RAWAT INAP PASIEN BPJS KESEHATAN DI RSI AISYIYAH KOTA MALANG - Kania, Salwa Adira Kania Adira; Ningrum, Herlinda Dwi; Wildan, Moh (Politeknik Kesehatan Kemenkes Malang, 2024)
Analysis of Factors Causing Incompleteness of Inpatient Medical Records of BPJS Health Patients at RSI Aisyiyah Malang City The incompleteness in filling out medical records often occurs in the handwriting of the attending physician (DPJP) that is difficult to read. Therefore, the casemix staff have to ask the responsible doctor again about it. When the doctor is in the room, errors in filling out the medical records can be corrected by the doctor directly, but sometimes the responsible doctor is not present, so no correction can be made to the medical records filling, resulting in pending claims. The research method used in this study is descriptive with an approach. Factors causing incompleteness of inpatient medical records of BPJS Health patients: a. Human Factors are caused by non-compliance, busyness of DPJP, and the handwriting of DPJP on the medical record form that is difficult to understand and read even though black ink ballpoints have been used. B. Method Factors are caused by procedures that are still not well implemented, resulting in incomplete medical records and no sanctions for this matter. C. Material Factors: no obstacles found for all materials or tools used are adequate. D. Machine Factors: there are no serious obstacles; even if there are obstacles in internet connection, it does not significantly affect the filling or claiming process. E. Environmental Factors: no obstacles found. F. Problem priority lies in human and method factors that cause incompleteness of medical records at RSI Aisyiyah. Keywords: Incompleteness of Medical Records, Inpatient Care, BPJS Health, Pending Claims, Hospital